“I would love for there not to be so many hoops … ”: recommendations to improve abortion service access and experiences made by Indigenous women and 2SLGTBQIA+ people in Canada - Renée Monchalin; Danette Jubinville; Astrid V. Pérez Piñán; Willow Paul; Madison Wells; Arie Ross; Kimberly Law; Meagan Chaffey; Harlie Pruder (Sexual and Reproductive Health Matters, 2023)
Acknowledging the barriers in accessing sexual and reproductive health services that disproportionately impact Indigenous women and 2SLGTBQIA+ people, coupled with the lack of knowledge surrounding Indigenous peoples’ experiences with abortion, we present qualitative findings from a pilot study investigating Indigenous experiences of accessing abortion services in Canada. We focus on findings related to participant recommendations for improving safety and accessibility of abortion services made by and for Indigenous people in Canada. Informed by an Indigenous Advisory Committee consisting of front-line service providers working in the area of abortion service access and/ or support across Canada, the research team applied an Indigenous methodology to engage with 15 Indigenous people across Canada utilising a conversational interview method, between September and November 2021. With representation from nine provinces and territories across Canada, participants identified with Anishinaabe, Cree, Dene, Haudenosaunee, Inuit, Métis and/ or Mi’kmaq Nations. Five cross-cutting recommendations emerged, including: (1) location, comfort, and having autonomy to choose where the abortion takes place; (2) holistic post-abortion supports; (3) accessibility, availability, and awareness of non-biased and non-judgemental information; (4) companionship, advocacy, and logistical help before and during the abortion from a support person; and (5) cultural safety and the incorporation of local practices and knowledges. Recommendations demonstrate that Indigenous people who have experienced an abortion carry practical solutions for removing barriers and improving access to abortion services in the Canadian context.